Stereospecificity of Microbial Hydrations of Oleic Acid to 10-Hydroxystearic Acid - Yang, Wei (1993)
We recently described a simple method for ascertaining the stereochemical purities of hydroxy fatty acids (S. H. El-Sharkawy, W. Yang, L. Dostal, and J. P. N. Rosazza, Appl. Environ. Microbiol. 58:2116-2122, 1992) based on the (1)H-nuclear magnetic resonance spectral analysis of diastereomeric S-(+)-O-acetylmandelate esters of hydroxystearates. This report describes the stereochemistries of microbial hydrations of oleic acid to 10-hydroxystearic acid by Nocardia aurantia (also known as Rhodococcus rhodochrous) ATCC 12674, Nocardia restrictus ATCC 14887, Mycobacterium fortuitum UI-53387, Pseudomonas species strain NRRL-2994, Pseudomonas species strain NRRL B-3266, and baker's yeast. 10(R)-hydroxystearic acid isolated from Pseudomonas species strain NRRL-2994 was the standard for use in the (1)H-nuclear magnetic resonance spectral technique to permit simple assignments of the absolute configurations of 10-hydroxystearic acid produced by different microorganisms. While the R. rhodochrous ATCC 12674-mediated hydration of oleic acid gave mixtures of enantiomers 10(R)-hydroxystearic acid and 10(S)-hydroxystearic acid, Pseudomonas species strain NRRL-B-3266 produced optically pure 10(R)-hydroxystearic acid. The remaining microorganisms stereoselectively hydrated oleic acid to 10(R)-hydroxystearic acid containing between 2 and 18% of the contaminating 10(S)-hydroxystearic acid.